INDONESIAN CULTURAL ANALYSIS IN THE SONG OF â€œLATHIâ€ BY WEIRD GENIUS - Khusna, Febriana Aminatul; Khoiruddin, Muhammad; Indriani, Giwang (Walasuji : Jurnal Sejarah dan Budaya, 2021)
Culture is something that cannot be separated in daily life. Thus, the importance of cultural preservation has become a major topic in the modern era. Music is a media that can be used to introduce the culture. This study aimed to investigate the Indonesian cultural elements contained in the song of "Lathi" by Weird Genius. This song was selected by the researcher due to its popularity in Indonesia like in Tik Tok, so that it became one of the most sought songs in 2020. To find out the research result accurately, the researcher applied descriptive qualitative method through content analysis approach. Visual, verbal, and instrumental analyses were the main focus of this research. The research result showed several cultural features in the song of â€œLathiâ€. Kuda Lumping, traditional dance, and Wayang Kulit) were found on its choreography. The elements of gamelan instruments and sentences that use Javanese were also present in the song. The song of â€œLathiâ€ put the elements of cultural preservation combined with contemporary art works. The result of this research was expected to increase cultural insight and increase the spirit of the younger generation in creating and preserving Indonesian culture.Â